THE EFFECT OF ANTHROPOMETRIC MEASUREMENT TRAINING ON POSYANDU cadres' KNOWLEDGE IN JOHAN PAHLAWAN DISTRICT - Redha Riska Fatwati; Teuku Muliadi; Itza Mulyani; Wardah Iskandar (PT. Radja Intercontinental Publishing, 2024)
Posyandu nutritional status monitoring activities are carried out by posyandu cadres. Quality anthropometric measurement results are influenced by the knowledge and skills of posyandu cadres. The aim of this research was to see whether there was an influence of anthropometric training on the knowledge of posyandu cadres. This research was carried out in Johan Pahlawan District, West Aceh Regency in November-December 2023. Using quantitative research methods and experimental research design with a Quasi Experimental design. The research sample was posyandu cadres in the Johan Pahlawan Community Health Center working area, with a sampling technique namely Multistage Random Sampling. Data processing uses Paired T-test. The results of this research showed a significant difference in the knowledge of posyandu cadres before and after training (p-value> 0.000), and there was an increase in the average value of knowledge of posyandu cadres, where the average value of knowledge before training was 78.62 and after training was 93.46. In conclusion, there is a significant influence between anthropometric training and the knowledge of poyandu cadres and there is a difference in the average knowledge of cadres before and after training for cadres in Johan Pahlawan District.